When IMA/EVM collides with systems administration - Pinto, Rossano P.; Pierini, Rodrigo A. A.; Teixeira, Caio; Rampazzo, Felipe J. A.; Pereira, Diego S.; Immich, Roger; Rothenberg, Christian E.; Henriques, Marco A. A. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2025)
This article does not have an abstract.